Mechanical force measures on uncooked beef longissimus muscle can predict tenderness of strip loin steaks - R.R. Timm; John A. Unruh; Michael E. Dikeman; M.C. Hunt; T.E. Lawrence; John E. Boyer; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 2002)
We investigated mechanical force measurements on uncooked longissimus muscle as a means to predict Warner- Bratzler shear force (WBSF) and trained sensory panel tenderness (SPT) of cooked strip loin steaks. Uncooked steaks from 24 USDA Select strip loins (IMPS 180) were evaluated at 2 and 14 days postmortem using plumb bob and needle probe devices attached to an Instron Universal Testing Machine. Cooked steaks aged 14 days were then evaluated for WBSF and SPT. Regression models to predict SPT from needle probe and plumb bob measurements individually taken at 2 days postmortem had R2 of 0.54 and 0.51, respectively. Combining needle probe and plumb bob measurements resulted in an R2 of 0.76; however, when quadratic terms for both variables were in the model, R2 was 0.80. Regressing needle probe and plumb bob measurements at 2 days postmortem with WBSF produced R2 of 0.51 and 0.45, respectively. When linear terms of both probes were combined, R2 improved to 0.77. An equation to predict WBSF including both the linear and quadratic terms of needle probe and plumb bob measurements resulted in R2 of 0.84. Using plumb bob and needle probe combined on uncooked longissimus muscle at 2 days postmortem can predict cooked WBSF and SPT of strip loin steaks aged for 14 days.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Longissimus dorsi; Instrument; Tenderness